Association of socio-demographic and socio-economic factors with consumer's decision-making in food purchases: a case study among low-income consumer during Covid-19 pandemic in Malaysia - Zainal Badari, Shamsul Azahari; Haron, Sharifah Azizah; Paim, Laily; Muhammad Arif, Afida Mastura; Zainudin, Norzalina; Abdul Rahim, Husniyah; Md Yusoff, Irwan Syah; Samsudin, Norhafifah (Human Resource Management Academic Research Society (HRMARS), 2023)
This study was conducted to determine how socio-demographic and socio-economic factors influenced the decision-making process of low-income households in Malaysia in food purchases during the pandemic. A total of 1791 low-income respondents were selected randomly through both online and face-to-face surveys conducted with strict procedures. The results revealed that most of the respondents were female (51.4%), Bumiputera (81.5%), aged between 25-30 and 31-40 (29.1%) with an average monthly household income between MYR1001-2000 (37.1%). Household needs (63.7%), price (39.9%), halal status (25.5%), and product quality (19.8%) were the critical factors that affected the decision-making. Additionally, the study found that the premises that offer low prices (33.1%), a variety of prices and brands (26.9%), and a diverse range of products (16.8%) were among the factors that influenced the respondents' decision-making. Respondents were classified into six types of consumer profiles: Hipsters, Confused, Quality-concerned, Planning, Hedonistic, and Habitual Consumers. Gender, age, marital status, household size, ethnicity, education level, household income, and occupation significantly influenced these six types of consumer profiles (p<0.05). In conclusion, low-income consumers were more focused on household needs, price, halal status, and product quality when making food purchase decisions, and socio-demographic and socio-economic factors played a critical role in influencing consumer decision-making.